A influência da criopreservação nas células mesenquimais indiferenciadas do ligamento periodontal de humanos análise comparativa in vitro - Vasconcelos, Rodrigo Gadelha (2011)
Cryopreservation is a process where cells or biological tissues are preserved by freezing at very low temperatures and aims to cease reversibly, in a controlled manner, all the biological functions of living tissues, i.e., maintain cell preservation so that it can recover with high degree of viability and functional integrity. This study aimed to evaluate the influence of cryopreservation on the mesenchymal stem cells originating from the periodontal ligament of human third molars by in vitro experiments. Six healthy teeth were removed and the periodontal cells grown in culture medium containing α-MEM supplemented with antibiotics and 15% FBS in a humidified atmosphere with 5% CO2 at 37° C. Cells isolated from each sample were divided into two groups: Group I - immediate cell culture (not fresh cryopreserved cells) and Group II - cell cryopreservation, during a period of 30 days. Analyses of rates of cell adhesion and proliferation in different groups were performed by counting the cells adhered to the wells, in intervals of 24, 48 and 72 hours after the start of cultivation. The number of cells in each well was obtained by counting viable cells with the use of hemocytometer and the method of exclusion of cells stained by trypan blue. The difference between groups for each of the times was analyzed by Wilcoxon test. Regarding the temporal evolution for each group, analysis was done by Friedman's test to verify the existence of differences between times and, when it existed, the Wilcoxon penalty was applied. The results showed no statistically significant difference between the two groups analyzed in this study. Therefore, we conclude that the cryopreservation process, after a period of 30 days, did not influence the cell type studied, and there was no difference in growth capacity in vitro between the groups